Small Side Game Training Contribution of Volume Oxygen Maximum Football Players Elite Pro Academy - Pamungkas, Hari; Nidomuddin, Muhammad; Yusuf, Havid; Mardikaningsih, Agusti; Lesmana, Heru Syarli (Journal of Sport Science and Education, 2023)
Small Side Games are a training method in which game situations are presented as real games, leading players to master technical, tactical and physical aspects. The research ability to maximize oxygen greatly affects performance of athletes in matches/games, because, with a poor physique, athlete's game can be detrimental to himself and team. The population of Bhayangkara U-18 men’s football players consisted of 25 people, especially football in wading through EPA (Elite Pro Academy) competition. This study usedexperimental method with one-group pretest-posttest design. The analysis technique used in this study was t-test with a significance level was 0.05. The average VO2Max pre-test for U-18 was 45.01 ml/kg/min, while the post-test VO2Max average was 49.92 ml/kg/min. The average difference between the two was 4.90 ml/kg/min. Monitoring and evaluation, regularly assess players' VO2Max levels to track improvements and adjust the training program accordingly. Frequency and duration at least two to three times a week in the training schedule. Each session should last for 20-30 minutes to ensure sufficient training stimulus. Consider playing position, performance goals, and physiological capabilities when designing small-side game sessions.